2021
DOI: 10.1021/acsmedchemlett.0c00369
|View full text |Cite
|
Sign up to set email alerts
|

Studying Histone Deacetylase Inhibition and Apoptosis Induction of Psammaplin A Monomers with Modified Thiol Group

Abstract: Psammaplin A (PsA) is a bromotyrosine disulfide dimer with histone deacetylase (HDAC) inhibition and acts through reduced monomer PsA-SH. We studied the connection of HDAC inhibition, cell growth inhibition, and apoptosis induction of PsA-SH by modifying the −SH group with deletion (6a) or replacement with hydroxamic acid (10b) or benzamide (12g). PsA-SH inhibits HDAC1/2/3 and 6a loses the HDAC inhibition ability. 10b inhibits HDAC1/2/3/6 while 12g shows selective inhibition of HDAC3. PsA-SH and 10b, but neith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…Previous studies revealed that psammaplin A is a natural prodrug that inhibits class I histone deacetylase [ 88 ]. In fact, the monomeric thiol form of psammaplin A was found to be exquisitely potent against HDAC1 in vitro with IC 50 of 0.9 nM [ 89 ]. Based on preliminary molecular docking simulations, we hypothesize that psammaplin A could be reduced to the active monomeric thiol form in the bacterial cell and binds to the LBD of LasR, preventing the binding of the native autoinducer, N -3-oxo-dodecanoyl-L-homoserine lactone.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies revealed that psammaplin A is a natural prodrug that inhibits class I histone deacetylase [ 88 ]. In fact, the monomeric thiol form of psammaplin A was found to be exquisitely potent against HDAC1 in vitro with IC 50 of 0.9 nM [ 89 ]. Based on preliminary molecular docking simulations, we hypothesize that psammaplin A could be reduced to the active monomeric thiol form in the bacterial cell and binds to the LBD of LasR, preventing the binding of the native autoinducer, N -3-oxo-dodecanoyl-L-homoserine lactone.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies of BTA compounds have shown this class of compounds as being promising candidates within the preclinical pipeline [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ]. Despite this, the large majority of BTAs from Verongiida sponges have been understudied when it comes to biological activity and function, leaving a potentially untapped resource for drug development.…”
Section: Resultsmentioning
confidence: 99%
“…Notable examples include the disulphide-linked psammaplins, first isolated from an unidentified specimen of Psammaplysilla Keller, 1889 (= Pseudoceratina Carter, 1885), in 1987 [ 24 ]. These compounds have inspired further studies of Verongiid sponges as well as the design of synthetically targeted anti-cancer drug libraries [ 25 , 26 , 27 ]. The BTA compounds from the Verongiid sponges show enormous pharmaceutical potential, with many viewed as being promising targets within the preclinical pipeline.…”
Section: Introductionmentioning
confidence: 99%
“…In bromotyrosine derivatives, such as psammaplin A monomers ( 102 ) and its analogs ( 103 ) (Baud et al 2012 ; Bao et al 2021 ), significance for the cytotoxicity effect of the free ketoxime group over the dimethylamine on 37 and 38 is evident. Besides the free ketoxime group, the cytotoxicity against the A549 cell line also leans towards a more straightforward structure of bromophenol in comparison to dibromomethoxyphenol moiety as present on 31 and 32 .…”
Section: Discussionmentioning
confidence: 99%